2018
DOI: 10.1038/s41437-018-0071-4
|View full text |Cite
|
Sign up to set email alerts
|

Human-mediated dispersal of cats in the Neolithic Central Europe

Abstract: Archeological and genetic evidence suggest that all domestic cats derived from the Near Eastern wildcat (Felis silvestris lybica) and were first domesticated in the Near East around 10,000 years ago. The spread of the domesticated form in Europe occurred much later, primarily mediated by Greek and Phoenician traders and afterward by Romans who introduced cats to Western and Central Europe around 2000 years ago. We investigated mtDNA of Holocene Felis remains and provide evidence of an unexpectedly early presen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 36 publications
(52 reference statements)
1
31
0
1
Order By: Relevance
“…Paleogenetic studies provide clear evidence that the first human mediated dispersal of F. s. lybica towards Europe stemmed from Anatolia, spreading towards current Bulgaria by 6,400 cal BP, Romania by 5,200 cal BP 24 and up to Poland by 5,000 cal BP 81 . Yet, archaeological evidence from Kastanas (3,300 cal BP) suggests that cat dispersal only reached continental Greece during the Late Bronze Age 24,82 .…”
Section: Discussionmentioning
confidence: 99%
“…Paleogenetic studies provide clear evidence that the first human mediated dispersal of F. s. lybica towards Europe stemmed from Anatolia, spreading towards current Bulgaria by 6,400 cal BP, Romania by 5,200 cal BP 24 and up to Poland by 5,000 cal BP 81 . Yet, archaeological evidence from Kastanas (3,300 cal BP) suggests that cat dispersal only reached continental Greece during the Late Bronze Age 24,82 .…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, through domestication, humans have deliberately altered feeding, behaviour, habitat and genetic heritage of multiple animal species (Wang et al ., 2013; Frantz et al ., 2020). During the course of evolution, dogs and cats were among the first animals to have undergone a long and extensive domestication process starting from their direct ancestors, the grey wolf and wild cat, respectively, leading to the selection of a wide range of canine and feline breeds (Savolainen et al ., 2002; Baca et al ., 2018). However, apart from animal phenotypic and genotypic alterations, several studies have demonstrated that the anthropogenic influence has significantly modified the intestinal microbiota of domesticated animals when compared to their close, yet wild relatives (Metcalf et al ., 2017; Alessandri et al ., 2019a–c).…”
Section: The Impact Of Human–pet Interplay On Gut Microbiota Compositmentioning
confidence: 99%
“…The reason why the NE cat appeared so far from its native range is still not clear. Baca et al (17) hypothesized that Late Neolithic NE cats in Poland, either still wild or already domesticated, followed the expansion northward of Neolithic farmers as their commensals. The geographic expansion of the NE cat was likely triggered by transformations of the landscape by Neolithic farmers, notably via deforestation (which created open environments similar to habitats exploited by the NE cat in its natural range) and the cultivation of crops, which increased the abundance of pest rodents (prey).…”
Section: Significancementioning
confidence: 99%
“…It is noteworthy that NE cats spread into regions already occupied by the native European wildcat, Felis silvestris silvestris. The NE cat is genetically distinct from the European wildcat (15); even their fossils can be easily distinguished with mtDNA analysis (17,18).…”
Section: Significancementioning
confidence: 99%